2003
DOI: 10.3758/bf03194817
|View full text |Cite
|
Sign up to set email alerts
|

The inability to ignore auditory distractors as a function of visual task perceptual load

Abstract: Using a response competition paradigm, we investigated the ability to ignore target responsecompatible, target response-incompatible, and neutral visual and auditory distractors presented during a visual search task. The perceptual load model of attention (e.g., Lavie & Tsal, 1994) states that task-relevant processing load determines irrelevant distractor processing in such a way that increasing processing load prevents distractor processing. In three experiments, participants searched sets of one (easy search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
114
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(143 citation statements)
references
References 21 publications
(81 reference statements)
21
114
8
Order By: Relevance
“…The selective enhancement of crossmodal distractor processing with increasing perceptual load observed here and by Tellinghuisen and Nowak (2003) stands in contrast to other studies in which increasing perceptual load in one modality either reduced distractor processing in another modality (Berman and Colby, 2002;Houghton et al, 2003;Klemen et al, 2009), or had no measurable effect (Parks et al, 2011;Rees et al, 2001). One factor that might have contributed to these different patterns of results is the nature of the load manipulations employed in each study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The selective enhancement of crossmodal distractor processing with increasing perceptual load observed here and by Tellinghuisen and Nowak (2003) stands in contrast to other studies in which increasing perceptual load in one modality either reduced distractor processing in another modality (Berman and Colby, 2002;Houghton et al, 2003;Klemen et al, 2009), or had no measurable effect (Parks et al, 2011;Rees et al, 2001). One factor that might have contributed to these different patterns of results is the nature of the load manipulations employed in each study.…”
Section: Discussioncontrasting
confidence: 54%
“…A similar positive relationship between perceptual load in one modality and distractor processing in another was reported by Tellinghuisen and Nowak (2003). They found that increasing visual perceptual load eliminated the flanker compatibility effect evoked by irrelevant visual flanker letters, but enhanced the flanker compatibility effects evoked by auditory distractors.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Indeed, there is some evidence that our rTMS protocol is inhibitory (Huang et al, 2005), and competition across modalities is a well known phenomenon (Tellinghuisen and Nowak, 2003;Lavie, 2005). We consider this account to be unlikely for two reasons.…”
Section: Possible Anatomical Basis Of Visual-olfactory Crossmodal Intmentioning
confidence: 99%
“…Even when people are performing a visual task, a novel audio stimulus tends to capture their visual attention [15]. In [16], it was shown that such cross-modal orienting occurs even when the detailed information about the visual target is provided in order to prevent uninformative audio cues from orienting attention.…”
Section: A Audio-visual Focus Of Attentionmentioning
confidence: 99%